PEMBELAJARAN EKONOMI SYARIAH MELALUI KLASIFIKASI KAIDAH-KAIDAH FIKIH DALAM FATWA DSN-MUI - Nur Faizin; Abdul Basid; Moh Rofiq (Institut Keislaman Abdullah Faqih Gresik, 2021)
Abstract: Sharia economic learning is a program that continues to be promoted in the context of optimizing fatwas so that they can be accepted by all groups. Fiqh principles are part of the â€œrememberingâ€ points in the DSN-MUI fatwa. This research examines the classification of the principles of fiqh in these fatwas according to the discipline of jurisprudence as part of the science of jurisprudence. This research is a library research. The research data in the form of DSN-MUI fatwas from 2000-2017 (116 fatwas) were collected using documentation techniques and analyzed using content analysis methods and then submitted descriptively-qualitatively. This study found that not all of the Basic Principles (al-Qawaid al-Asasiyyah) were used in the DSN-MUI fatwas; the mention of Fiqh principles is not hierarchical; editors of the hadiths that have become rules; Ushul's rules; and the inadequate use of fiqh principles in fatwas. In the context of learning Islamic economics with literacy and optimizing fatwas, the research recommends the maximum use of fiqh principles, both al-Qawaid al-Asasiyyah, al-Qawaid al-Far`iyyah, and al-Qawaid al-Kulliyyah.Keyword: Fatwa, DSN-MUI, Skonomi Syariah